Combining the basic principles of the classical art school with the unique national consciousness of the mongolians - Byambajav, Sarantuya (Mongolian Journal of Arts and Culture, 2023)
Academism refers to the preservation of the style of art and sculpture created under the influence of the European art academies in the 19th century. Academic art is, in a sense, closely related to the same aesthetic norms as classical concepts. Although smaller works such as portraits, landscapes, and still lifes are popular (and often sell more easily), audiences and critics often value large paintings of vintage, natural, and historical moments the most. From the above, learning academic art and creating an approved work means long-term hard work and unparalleled talent. But Otgontuvden Badam is a clear representative of the vital history of academic art, who has gone through this hard work, demonstrated his genius, and combined the basic principles of the classical school with the unique national consciousness of Mongolians. Сонгодог сургуулийн суурь зарчмуудыг монголчуудын үндэсний онцгой ухамсартай хослуулах нь. Хураангуй: Академизм гэдэг нь 19-р зуунд европын урлагийн нөлөөн дор бий болсон урлаг юм. Академик урлаг нь нэг ёсондоо сонгодог ойлголттой адил гоо зүйн хэм хэмжээнүүдтэй нягт холбоотой байдаг. Хэдийгээр хөрөг, байгаль, натюрморт зэрэг төрөл зүйлүүд түгээмэл байдаг ч үзэгчид болон шүүмжлэгчид материаллаг шинж чанар, чимэглэл, байгалийн болон түүхэн агшинг хар уулсан том зургуудыг хамгийн их үнэлдэг. Энэ бүгд ээс үзэхэд, академи урлагт суралцаж, батлагдсан бүтээл туурвина гэдэг урт хугацааны шаргуу хөдөлмөр, хат уужил, хосгүй авьяас гэсэн үг. Харин Бадамын Отгонтүвдэн бол энэхүү нөр их хөдөлмөрийг туулж, авьяас билгээ хар уулж, акаде ик сургалт ын үндсэн зарчмуудыг монгол хүний үндэсний өвөрмөц ухамсартай хослуулсан , эрдмийн урлагийн амин чухал түүхийн тод төлөөлөгч болсон уран бүтээлч юм. Түлхүүр үг: академизм, сонгодог урлаг, үндсэн зарчим